Crime prevention theory and practice - Schneider, Stephen (CRC Press, Taylor & Francis Group, 2015)
The book presents a comprehensive overview, a detailed discussion of each of the dominant crime prevention strategies, and an examination of the role of the police and other government agencies in crime prevention.